2010
DOI: 10.1038/hr.2010.24
|View full text |Cite
|
Sign up to set email alerts
|

A new systolic parameter defined as the ratio of brachial pre-ejection period to brachial ejection time predicts overall and cardiovascular mortality in hemodialysis patients

Abstract: Impaired left ventricular systolic function is an important cause of mortality in hemodialysis patients. An increase in the ratio of pre-ejection period (PEP) to ejection time (ET) is associated with a decrease in left ventricular systolic function. Brachial PEP (bPEP) and brachial ET (bET) can be automatically determined from an ankle-brachial index (ABI)-form device. The aim of this study was to investigate whether bPEP/bET was a useful predictor for overall and cardiovascular mortality in hemodialysis patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
2
11
1
Order By: Relevance
“…11 In addition, our recent study also showed the bPEP/bET, but neither bPEP nor bET, was an independent predictor for CV and overall mortality in hemodialysis patients. 12 In the present study, we found that the bPEP/bET, but neither bPEP nor bET, was an independently predictor of CV events in CKD patients, which was consistent with previous findings. It implies that patients with increased bPEP/bET, a marker of left ventricular systolic dysfunction, might be a high risk group for increased CV events in patients with CKD.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…11 In addition, our recent study also showed the bPEP/bET, but neither bPEP nor bET, was an independent predictor for CV and overall mortality in hemodialysis patients. 12 In the present study, we found that the bPEP/bET, but neither bPEP nor bET, was an independently predictor of CV events in CKD patients, which was consistent with previous findings. It implies that patients with increased bPEP/bET, a marker of left ventricular systolic dysfunction, might be a high risk group for increased CV events in patients with CKD.…”
Section: Discussionsupporting
confidence: 82%
“…12 However, there was no study to evaluate the relationship between bPEP/bET and CV outcome in patients with CKD. The aim of this study was to investigate whether bPEP/bET is a useful predictor of CV events in patients with CKD.…”
Section: Bpep/bet Predicts CV Events In Ckd Patientsmentioning
confidence: 99%
“…Patients with reduced Ea and Sa values, in particular, have a poor prognosis [26]. Besides, left ventricular and left atrial size, left ventricular hypertrophy and left ventricular systolic function were reported to be able to predict CV outcomes [27][28][29][30]. In this study, although Ea, Sa, left ventricular dimensions, LAVI, LVMI, and LVEF were associated with increased CV events in the univariate analysis, the association became insignificant after the multivariate analysis.…”
Section: Discussioncontrasting
confidence: 62%
“…The bPEP/bET ratio has been reported to be an independent predictor of adverse outcomes in patients with kidney disease, including CV events in patients with CKD stage 3-5 [59], and overall and CV mortality in patients receiving HD [60]. Therefore, screening patients with kidney disease using the bPEP/bET ratio may help to identify patients at high risk of CV events [59].…”
Section: The Ratio Of Brachial Pre-ejection Period (Bpep) To Brachialmentioning
confidence: 99%